Bad Dreams Under Alternative Anchors : Are the Consequences Different? - Auernheimer, Leonardo (IMF Working Papers; Working Paper ;, 2000)
Using a simple model, this paper shows how a strict monetary rule exhibits characteristics similar to those of an exchange rate anchor, in terms of a lack of robustness in the presence of adverse expectations ('bad dreams'). More specifically, as an anticipated devaluation under an exchange rate rule leads to well-known contractionary effects, an anticipated increase in the money stock under a monetary rule, though initially expansionary, becomes contractionary when these expectations are not validated. This suggests that much of the criticism of an exchange rate anchor implicitly considers not another rule but rather, discretion as the alternative.